Cortical thickness of the tibial diaphysis reveals age- and sex-related characteristics between non-obese healthy young and elderly subjects depending on the tibial regions - Maeda, Keisuke (J Exp Orthop, 2020)
PURPOSE: This study aimed to evaluate the age- and sex-related characteristics in cortical thickness of the tibial diaphysis between non-obese healthy young and elderly subjects as reference data. METHODS: The study investigated 31 young subjects (12 men and 19 women; mean age, 25 ± 8 years) and 54 elderly subjects (29 men and 25 women; mean age, 70 ± 6 years). Three-dimensional estimated cortical thickness of the tibial diaphysis was automatically calculated for 5000–9000 measurement points using the high-resolution cortical thickness measurement from clinical computed tomography data. In 12 assessment regions created by combining three heights (proximal, central, and distal diaphysis) and four areas of the axial plane at 90° (medial, anterior, lateral, and posterior areas) in the tibial coordinate system, the standardized thickness was assessed using the tibial length. RESULTS: As structural characteristics, there were no differences in the medial and lateral thicknesses, while the anterior thickness was greater than the posterior thickness in all groups. The sex-related difference was not shown. As an age-related difference, elderly subjects showed greater or lesser cortical thickness than the young subjects, depending on the regions of the tibia. CONCLUSIONS: Cortical thickness was different depending on sex, age, and regions in the tibia. The results of this study are of clinical relevance as reference points to clarify the causes of various pathological conditions for diseases. LEVEL OF EVIDENCE: Level 3.